Mimesis, Gestures And The Origin Of Neumes In Adorno’s Towards A Theory Of Musical Reproduction (Brief Remarks) (Per Musi, 2021)
Although the paleographical approach remains essential in the scholarly research focused on the origins, dissemination, and functions of the earliest notational systems used in medieval plainsong, historical Musicology is open to new methodologies. This article seeks to analyse some topics about the origins of chant notation from the perspective of the critical theory of Theodor W. Adorno. In his unfinished “Towards a Theory of Musical Reproduction”, Adorno reflected on the specificities of the notational system, which he sought to comprehend in light of the nuclear concept of Mimesis. For him, "the musical symbols chosen to wrest the music are images of gestures", serving the function of social control. Nonetheless the progressive rationalization of music (indispensable for its aesthetic autonomy) has faded its mimetic dimension, the former continues to be remarkable on the graphic signs. It seems important to critically (re)adress this challenging and interpellant theoretical discourse.